Dynamic construal of conceptual categories: An investigation of the Southern Vietnamese classifier cây - Abusalim, Nimer (Dirasat: Human and Social Sciences, 2021)
While conceptual categories have been a topic of much research, it has yet to be resolved whether or not conceptual categories have a static underlying mental representation and fixed category membership, or a dynamic mental representation with variable membership. Natural language classifiers have often been looked at as sources of evidence for conceptual categories. This paper investigates the Southern Vietnamese classifier cây and, through a hierarchical organization task methodology, provides evidence for the view that the underlying mental representation of conceptual categories is to some degree dynamic. Our data shows the classifier cây being used in metonymic and metaphoric expressions and to form ad hoc categories. These results challenge the static view of category mental representation, which predicts that such uses of the classifier cây should not be possible.